Binding of Radioactive Benzylpenicillin to Sporulating Bacillus Cultures: Chemistry and Fluctuations in Specific Binding Capacity - Lawrence, Paul J. (1971)
The chemistry of the binding of (14)C-benzylpenicillin to sporulating cultures of Bacillus megaterium and B. subtilis is similar to that in a 4-hr vegetative culture of Staphylococcus aureus. Unlabeled penicillins prevent the binding of (14)C-benzylpenicillin, but benzylpenicilloic acid and benzylpenilloic acid do not. Bound antibiotic can be removed from cells with neutral hydroxylamine at 25 C. Sporulating cultures display two intervals of enhanced binding, whereas binding to stationaryphase S. aureus cells remains constant. The first period of increased binding activity occurs during formation of the spore septum or cell wall primordium development, and the second coincides with cortex biosynthesis.